IMPACT OF ECONOMIC AND LEGAL THEORIES TO TAX SYSTEM - Golts, Edgars (Administrative and Criminal Justice, 2023)
This work is part of the author's research dissertation of evidence in tax law framework. The development of the modern world and the situation which is rapidly changing, the increasing role of the geopolitical risk conditions obtained legal order, including a clear and understandable tax system, which is based on theoretical knowledge of economic and legal science. The article addresses the issues which are relating to the theoretical aspects of the economic and legal sciences. The author of this article, when economists knowledge about tax system compared with the scientific view of tax law. The author concludes that it is very much a common scientific conclusions, although of the same substance with different terms used for form. The article is viewed as part of the historical developments, as it sees economic scientists. Analysing the economic nature of the tax system the author touching many of economic aspects, in order to better enable them to compare with legal.